Seismic performance analysis of braced steel structures based on vibration experiments and finite element simulation - Nan Cui; Shuangshuang Liu (PLoS ONE, 2025)
The study analyzes the seismic performance of spatial steel frame structures by creating a three-dimensional nonlinear finite element model and designing vibration table model experiments. This is done to ensure the seismic performance of the steel framing-bracing system in spatial steel frame structures and to raise the level of seismic and disaster prevention technology of steel structures. The outcomes revealed that under the experimental load consisting of simulated seismic waves generated by the shaker, the initial natural frequencies of the bidirectional bracing arrangement in white noise in the X and Y-directions were larger, 53.18 Hz and 72.49 Hz, respectively. The decrease of the vibration frequency of the bidirectional bracing arrangement structure was smaller under the increase of the excitation acceleration. In El Centro seismic waves, Taft seismic waves and Wenchuan seismic waves, the changes of damping ratio, acceleration amplification factor and relative displacement of bidirectional bracing arrangement were smaller than those of unidirectional bracing arrangement. The bidirectional bracing was beneficial to the overall stiffness and seismic performance of the structure, and helps the steel frame structure to resist lateral displacement. At the same time, the bidirectional support was more favorable to the seismic performance if the support structure was arranged according to the wave, which could effectively reduce the strain. Under the simulated seismic action of the 3D non-linear finite element model, the finite element model results were tested by inputting the parameters of Wenchuan seismic wave, the fit between the finite element model results and the vibration table experiment results was high, and the acceleration time-course curve and displacement time-course curve were basically the same. The simulation errors of the maximum values of acceleration and displacement were 7.0% and 4.0%, and some of the larger errors were within the acceptable error range. This study provides reference and theoretical guidance for the research on the seismic performance of steel framing - bracing system under seismic action, which is conducive to the expansion of the application field of steel seismic structures.